2019
DOI: 10.3390/qubs3010004
|View full text |Cite
|
Sign up to set email alerts
|

The Helical Magnet MnSi: Skyrmions and Magnons

Abstract: Since the late 1970s, MnSi has played a major role in developing the theory of helical magnets in non-centrosymmetric materials showing the Dzyaloshinsky-Moriya interaction (DMI). With a long helimagnetic pitch of 175 Å as compared to the lattice d-spacing of 4.55 Å, it was ideal for performing neutron studies, especially as large single crystals could be grown. A (B-T)-phase diagram was measured, and in these studies, under the application of a field of about 180 mT perpendicular to the scattering vector Q, a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…It is reported to evince the chiral modulations caused by the competition between D ij and J ij energies, apart from exhibiting prototypical itinerant magnetism in which the same electrons are responsible for both magnetism and conduction. Such chiral modulations are manifested into the formation of hexagonal structured skyrmion lattice under the influence of small magnetic fields below the ordering temperature T hel [17][18][19][20][21]. In addition, the magnetic interactions in MnSi are long-range governed by the tricritical exponents.…”
Section: Introductionmentioning
confidence: 99%
“…It is reported to evince the chiral modulations caused by the competition between D ij and J ij energies, apart from exhibiting prototypical itinerant magnetism in which the same electrons are responsible for both magnetism and conduction. Such chiral modulations are manifested into the formation of hexagonal structured skyrmion lattice under the influence of small magnetic fields below the ordering temperature T hel [17][18][19][20][21]. In addition, the magnetic interactions in MnSi are long-range governed by the tricritical exponents.…”
Section: Introductionmentioning
confidence: 99%
“…The number of publications reached more than 2000 and citations rose to some thousands per year recently. The early developments in this field are the topic of the review [3]. Interestingly, Muon spin rotation (µSR) spectra recorded for manganese silicide MnSi in [4] showed that the magnetic structures of MnSi in zero-field at a low temperature and in the conical phase near the magnetic phase transition deviate from the expected helical and conical structures.…”
mentioning
confidence: 99%